Evaluating the level of performance according to the tax diagnosis TADAT: applied research in the General Tax Authority (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The aim of the research is to indicate the degree of arrangement of the tax branches discussed and the level of efficiency of their performance according to the dimensions approved in the tax diagnostic tool (TADAT). The checklist has been approved as a main tool in collecting data and information from the tax branches of the General Authority for Taxes and the number (8) branches represented by (Karrada , Karakh Center, Al-Rusafa, New Baghdad, Al-Dora, Karakh Al-Tafim, Al-Kadhimiya, Al-Bayaa),  The statistical program (spss) was used to calculate the weighted arithmetic media, and we reached the research to a number of conclusions, the most important of which were: - Each of the subsections (Karkh Al-Ahram and Karrada) achieved an evaluation level with a high degree of efficiency, which indicates its ability to use its available resources efficiently. Whereas, the researched branches (Karkh Center, New Baghdad, Kadhimiya, Al-Rusafa, Al-Bayaa, Al-Dora) achieved a level of performance efficiency with a moderate degree.